Automatic Cat Feeding System Based On The Internet Of Things (IoT) With Time And Feed Weight Control - Wijayanti, Sefi Ayuk; Maulindar, Joni; Nurohman, Nurohman (Politeknik Negeri Lhokseumawe, 2025)
A common problem in pet cat care is irregular feeding, which can affect the animal's nutritional balance and health. To address this issue, an Internet of Things (IoT)-based automatic feeding system utilizing an ESP32 microcontroller has been developed. The system integrates a Passive Infrared (PIR) sensor for cat motion detection, a Load Cell for measuring food weight, and an ultrasonic sensor to monitor food stock levels. Data is stored and displayed through a web-based platform that supports meal scheduling and real-time monitoring. System testing using a blackbox approach shows that all components function properly, including time synchronization via NTP, Wi-Fi communication, and overall sensor functionality. This system is expected to improve feeding consistency and optimally support the health and well-being of cats.